The Quality Management of Higher Education on the Job Performance of Lecturers Basis - Lisnasari, Srie F (Advances in Social Sciences Research Journal, 2018)
The quality management of higher education depends on human resources quality. The objective of this research was concerning with the Quality management of Indonesian higher education that involved the effect of self-efficacy, rewards and work motivation on job performance. This research was conducted in Medan Municipal by using a survey methods with path analysis applied in testing hypothesis. It involved 79 head of departments in higher education as respondents who were selected by proportional random sampling. This research findings were as follows: (1) There was a direct effect of self-efficacy on job performance, (2) There was direct effect of rewards on job performance, (3) There was a direct effect of work motivation on job performance, (4) There was direct effect of self-efficacy on work motivation, (5) There was direct effect of rewards on work motivation. Therefore, job performance could be improving by rising the self-efficacy, rewards and work motivation.